2019
DOI: 10.1177/2059799119840982
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative comparative analysis in educational policy research: Procedures, processes, and possibilities

Abstract: In educational policy research, linking specific practices to specific outcomes is an important (though not the only) goal, which can bias researchers (and funders) toward employing purely quantitative methods. Given the context-specific nature of policy implementation in education, however, we argue that understanding how specific practices lead to specific outcomes in specific conditions or contexts is critical to improving education. Qualitative comparative analysis is a method of qualitative research that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This study aims to identify, compare, and analyse similar and different characteristics of the selected doctoral programs in different universities in Türkiye and Canada having different educational systems. Therefore, it employs qualitative comparative research methodology, aiming to understand, reveal, and delineate the dynamics of educational policy, plan, and reform initiatives within selected contexts that could positively affect the current view of education from a comprehensive perspective (Bingham, Dean & Castillo, 2019). Due to its structural and contextual characteristics, this study is an example of comparative education research.…”
Section: Methodsmentioning
confidence: 99%
“…This study aims to identify, compare, and analyse similar and different characteristics of the selected doctoral programs in different universities in Türkiye and Canada having different educational systems. Therefore, it employs qualitative comparative research methodology, aiming to understand, reveal, and delineate the dynamics of educational policy, plan, and reform initiatives within selected contexts that could positively affect the current view of education from a comprehensive perspective (Bingham, Dean & Castillo, 2019). Due to its structural and contextual characteristics, this study is an example of comparative education research.…”
Section: Methodsmentioning
confidence: 99%
“…Exploration is also found in literature to be a significant part of comparative studies so as to maintain the evidence-based approach (Esser & Vliegenthart, 2017;Takwoingi, Leeflang, & Deeks, 2013). Also, for making the comparative account of the educational policies explorative type of studies are found to provide best outcomes (Bingham, Dean, & Castillo, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Policy implementation is context-specific in nature (Bingham et al, 2019). Therefore, it is more important to learn "what conditions made a policy work" instead of simply borrowing a policy from another country.…”
Section: Learning From the Italian Experiencementioning
confidence: 99%